THE EFFECT OF MERCURY ON SOME ASPECTS OF LIFE FOR TWODIETARY LEVELS THE ALGAE CHLORELLA VULGARIS ANDCRUSTACEAN ANIMAL SIMOCEPHALUS VETULUS - Abdelmunem, Wessal (Iraqi Journal of Science, 2024)
The present study included the effect concentrations of mercury element (0.05-0.2) mg/l on algae Chlorella vulgaris. The data showed decrease cells number,growth rate and increase inhibition rate with increasing mercury concentration andthe elongate of exposure period which showed the toxicity of the element. Also theresults showed the toxic effect of mercury at concentrations (0.01-0.05) mg/l on theanimal Simocephalus vetulus, by decreasing the longevity rate, growth rate,fecundity, fertility, number of brood per female during 21 days compared to thecontrol.